Essentials Counselling Skills for Community Health Workers: Supporting Pregnant Adolescents - Rakgadi G. Malapela; Sheillah H. Mboweni; Patrone R. Risenga (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Background: Counselling is crucial to provide support to pregnant adolescents during these challenging times. Adolescent pregnancy has significant global implications. It endangers the lives of the mother and the unborn child, contributing to maternal and child morbidity and mortality rates. Furthermore, it threatens the achievement of sustainable development goals of ending poverty (Goal 1), zero hunger (Goal 2), providing good health care (Goal 3), quality education (Goal 4), empowerment of women and girls (Goal 5), providing decent jobs and promoting economic growth (Goal 8). Community health workers (CHWs) play a role in empowering adolescents through counselling skills, thus promoting informed decision-making for better outcomes. Aim: The study aims to evaluate the counselling skills of CHWs in their efforts to support pregnant adolescents (PA) in Limpopo province. Setting: The research was carried out with CHWs in the Mopani and Vhembe districts of the Limpopo province in South Africa. Methods: A quantitative descriptive approach was used to evaluate CHWs’ counselling skills for PAs in Limpopo. The study included CHWs who were actively involved in addressing AP issues within the community. A sample of 81 respondents was selected using simple random sampling. Ethical approval was obtained. Data were collected from July to October 2022 using a questionnaire guided by the Theory of Reasoned Action. Descriptive statistics were analysed using Statistical Package for Social Scientists version 24. The questionnaire’s validity was assessed using Cronbach’s alpha, resulting in a correlation coefficient of 0.710. Results: Most of the participants were from the Mopani district (63%), while the remaining (32%) were from the Vhembe district. Females constituted many participants (87.7%), while males accounted for only 9% with 1.2% not responding. The study identified significant variations in counselling recommendations. Preparation: Using private space with fewer distractions showed considerable variability (standard deviation = 0.218). Introduction: High variability was observed in using the SOLER method (standard deviation = 0.316). Working phase: Suggesting rather than advising had notable variability (standard deviation = 0.396). Termination: Avoiding abrupt endings and informing clients about the session’s conclusion demonstrated variability (standard deviation = 0.283). Additionally, the majority (64%) of the participants found record-keeping unnecessary, which demonstrated the highest variability (standard deviation = 0.482). Conclusion: Counselling plays a crucial role in positively impacting the lives of PAs and their unborn children. The study revealed CHWs’ proficiency in counselling techniques and emphasised the importance of following the counselling stages.